MiR-125b-5p ameliorates hypoxia/reoxygenation-induced endothelial cell dysfunction and attenuates reduced uterine perfusion pressure-induced hypertension in pregnant rats via targeting BMF - Haoyu Zheng; Zhou Yu; Hairong Wang; Hongxue Liu; Xiaoqin Chen (Hypertension in Pregnancy, 2022)
Background and Purpose MicroRNA-125b-5p (miR-125b-5p) is downregulated in patients with gestational hypertension signs. However, the role of miR-125b-5p in pregnancy-induced hypertension (PIH) remains unknown. Methods The human placental microvascular endothelial cells (HPMECs) have undergone hypoxia and reoxygenation (H/R) treatment to establish PIH cellular model. Rats were performed with reduced uterine perfusion pressure (RUPP) operation to establish PIH animal model. Results MiR-125b-5p promoted viability while inhibited the apoptosis of H/R-treated HPMECs by downregulating BMF. MiR-125b-5p alleviated hypertensive symptoms and improved pregnancy outcomes in RUPP rats. Conclusion MiR-125b-5p ameliorates H/R-induced HPMEC dysfunction and attenuates RUPP-induced hypertension in pregnant rats by downregulating BMF.